2006
DOI: 10.1086/504323
|View full text |Cite
|
Sign up to set email alerts
|

Use of Efavirenz Is Not Associated with a Higher Risk of Depressive Disorders: A Substudy of the Randomized Clinical Trial ALIZE-ANRS 099

Abstract: The frequency of depressive disorders was high in this population, but the disorders were not related to EFV treatment. Younger age and a history of depression are important determinants for depression and should be considered for early detection and case management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…The same study indicated that the 600-mg dose of EFV is associated with a high rate of adverse events that could lead to discontinuation, which suggests that the lower dose of 400 mg may be almost as effective without the high discontinuation rate. In the present study, associated with the dose-reduction regimen, a significant number of patients experienced improvement of CNS symptoms, which was unexpected on the basis of previous reports [5,21,22]. Interestingly, some of these patients did not appreciate their clinical state and considered themselves to have no CNS-related symptoms during the standard-dose treatment.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The same study indicated that the 600-mg dose of EFV is associated with a high rate of adverse events that could lead to discontinuation, which suggests that the lower dose of 400 mg may be almost as effective without the high discontinuation rate. In the present study, associated with the dose-reduction regimen, a significant number of patients experienced improvement of CNS symptoms, which was unexpected on the basis of previous reports [5,21,22]. Interestingly, some of these patients did not appreciate their clinical state and considered themselves to have no CNS-related symptoms during the standard-dose treatment.…”
Section: Discussionsupporting
confidence: 76%
“…However, after the dose reduction, they reassessed the status and evaluated symptoms during the treatment with the standard dose as associated with CNS symptoms and indicated that the reduced dose of EFV relieved them of such symptoms. Because EFV-treated patients often stick to the regimen, previous reports of symptom questionnaires conducted during the standard treatment might have underestimated the EFV-associated CNS symptoms [5,21,22]. However, this finding might be confounded by placebo effect, because the patients were told that their EFV levels were high while receiving the initial dose and decreased throughout the dose-reduction protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, depression occurred at similar but low rates in both the RPV and EFV groups. Data from previous studies that evaluated depression in patients treated with EFV are conflicting, with some investigators reporting a link between increased depression and EFV [19,21,42], while others failed to find any such association [20,43,44]. Patients who discontinue highly active ARV therapy because of AEs do so mainly within the first few months following therapy initiation [3,45].…”
Section: Tolerability Of Rilpivirine Vs Efavirenz 395mentioning
confidence: 99%
“…12 Depressive disorders among PLHIV were also thought to be related to the use of the antiretroviral drug efavirenz, but this was disputed by a large study in 2005. 13 Optimal adherence to antiretroviral therapy (ART) is essential for viral suppression and positive treatment outcomes. 14 The negative impact of depressive disorders on adherence to ART has been demonstrated in developed countries.…”
Section: Introductionmentioning
confidence: 99%